Evaluation of an intervention in general practices to strengthen social activities in older patients - a qualitative study of patients’ experiences in the project HoPES3 - Mächler, Ruth; Frick, Eckhard; Sturm, Noemi; Stolz, Regina; Valentini, Jan; Straßner, Cornelia (Patient education and counseling, 2023)
Objective - In the research project HoPES3, the effectiveness of a multifaceted intervention, where one of the aims was to encourage social activities among older patients, was investigated in a cluster-randomised controlled trial. Patients were offered a conversation about their spirituality (spiritual history) which also included questions about their social relationships. The aim of this study was to examine patients’ experiences regarding the acceptability, feasibility, conversational content and perceived benefits and harms of the interventions focusing on social relationships and activities. - Method - Semi-structured interviews with 29 patients of the intervention group aged 70 years or older. - Results - Loneliness in old age is the result of a long history with underlying complex reasons. Activities proposed by the practice team were rarely carried out, but if they were, patients reported strong benefits. Patients reported their GPs’ interest in their lives had resulted in a more trusting doctor-patient relationship. Almost all patients recommended to implement the intervention in general practices. - Conclusion and practice implications - When raising the topic of loneliness, it is crucial to give patients the opportunity to explain the biographical developments which led to their situation. Therefore, embedding the conversation into a broader context such as a spiritual history might be helpful.
Online verfügbar 13 November 2022, Artikelversion 24 November 2022
Gesehen am 30.01.2023